Craniometric guidance for the Sylvian vein - Kim, Chang Heon; Kim, Hyo Joon; Lee, Robert Seungbok (Frontiers in Neuroscience, 2025)
ObjectivesThe Sylvian vein (SV) is the primary anatomical landmark on the lateral surface of the brain. For the neurosurgical approach, recognizing the SV is essential information. With the trend toward minimally invasive surgery, precise anatomical localization becomes increasingly important. Moreover, a craniometric guidance for the SV will reliably enhance neurosurgical planning and intraoperative approach. Anatomical guidance for the SV was previously proposed, and it utilized a linear bar type. However, its representation was complex and unclear. Thus, we aimed to develop a new guidance for the SV.Materials and methodsThe SV of thirty-seven patients was illustrated on venous phase angiographic images. Scanned images were manually fused using Adobe Photoshop CS5. The outlines of the lateral skulls were realigned to fit together, after which venous structures were overlaid. Coronal sutures and posterior clinoid processes served as references during this realignment process. Half the length of the line connecting the external ear canal (EAC) and glabella was used to draw a circle (Sylvian circle). The Sylvian circle (SC) and the actual course of the SVs were then compared. The SV and SC distributions were measured using ImageJ (NIH).ResultsTwenty-nine (79%) of the thirty-seven patients exhibited SV located within 5 mm of the SC. Five SVs were positioned above the SC, and two were placed below it. There was a total of seven cases in which the trajectory was within 5 mm of the SC and accounted for less than 80% of the path.ConclusionThe SC represents the contour of the SV more accurately than a straight line. The SC can be drawn promptly and is instinctively applicable in pre- and intra-operative neurosurgical practice.